A Preliminary Study on Chemical Properties of Soil of Pakhal Wild Life Sanctuary, Telangana, India - Jyothi , P.; Kumari , Y. Sunila (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Plant growth depends on fertility and nutrient status of the soil. Presence of optimum range of these nutrients is inevitable for the growth survival of the flora. The present study was conducted during June 2021- June 2022 to know the chemical properties of black and red soils of the Pakhal wild life sanctuary, Telangana, India. Soil variables like PH, EC, organic matter, N, P, and K were assessed to know soil fertility. The study revealed the PH of the soil samples was 7.2 and it was on slightly alkaline. The values of EC observed in the present study were 0.10 and 0.75 dS /m respectively for black and red soils. Soil organic carbon analyzed was 0.61 for the black soil and it was 0.51 for red soil. The amount of available nitrogen was 213 and 226 kg/ha respectively for black and red soils. The phosphorus content of black soil is 32.61 kg/ha and for red soil it was 16.29 kg/ha. Potassium was reported to be 396 kg/ha and 517 kg/ha respectively for black and red soils. The study revealed that the soil is favorable for the growth of the plants.